ELECTRONIC SIGNATURE ON THE SALE AND PURCHASE AGREEMENT FROM CIVIL LAW PERSPECTIVE - Nabila Nabila (Universitas Muhammadiyah Gresik, 2022)
In the current technological developments, some companies use electronic media to certify documents through digital media. Based on article 1320 of the Civil Code, the agreement will be valid when 2 conditions are met, namely subjective conditions and objective conditions. But on the other hand, the electronic transaction agreement between PT. Fight for Nature with Australian Rural Exports Pty. Ltd. using digital hands is legal and has legal consequences. The focus of the study in this scientific paper is related to the validity of the electronic signature of an agreement in the perspective of civil law and the legal consequences of agreements made online/electronically when one of the parties defaults/breaches promise. The legal research method used in this research is normative juridical. The results of this study indicate that the process of the occurrence of electronic commerce transactions is carried out with 4 stages of agreement theory, namely offer, acceptance, payment, and delivery. The validity of electronic signatures in an agreement in the perspective of civil law is by referring to the National Electronic Transaction information law and Government Regulations as implementing regulations for Electronic Transactions, which are linked to the principles of agreement in the Civil Code. In addition, the legal consequences of online/electronic engagements when one of the parties is in default/breach of promise is that the judge can request a cancellation of the agreement as a legal consequence or legal consequence of a default in an online sale and purchase agreement..